Challenges ahead for Bulgarian’s competitiveness as a mountain tourism destination - Mariya Stankova (Tourism & Management Studies)
A re-examination of the concept of tourism reveals new dimensions and draws specialists’ attention to its multi-directional social influences. Tourism is one of the fastest growing industries in the global economy, fostering economic development worldwide. It is recognised that tourism must be developed and managed in a controlled, integrated and sustainable manner. With a joint effort, an attempt could be made to realise objectives like improvement of quality, competiveness and sustainability of tourism products offered regardless of the particular scale – national, regional, or international – by “pursuing” tourists’ needs. However, this paper is focused on the priority given to the tourism industry in the economic development of the Republic of Bulgaria in bid to position the country well on the international level of competitiveness. This necessitates research on the opportunities of tourism and the economy of Bulgaria to help attain the competitiveness within the context of sustainable development.